The role and impact of the influencer marketing strategy in fashion companies: Farfetch case study - Mekkaoui, Sarah (2022)
Lately, we’re seeing a turning point in digital marketing, with the growing interest in digital influencers, whose mission is to share their opinions and thoughts on different brands or products with what we call ‘followers’ on different social media platforms. At first, this strategy has been fiercely contested, and many marketers were not sure of its effectiveness. It is by seeing more and more successful companies entirely basing their social media approach on these influencers, that it has officially now become proper marketing expertise. In this in-company project, the influencer marketing strategy of the online luxury marketplace FARFETCH will be analyzed to understand the importance this strategy can have in fashion companies. A literature review will help to identify the key aspects and concepts of this social media strategy. Moreover, an online survey on social media usage and influencer marketing allowed us to gather a strong database about the subject. A total of 126 answers have been collected and analyzed. This survey helped to highlight areas that Farfetch has not exploited yet and which could be considered as solutions and potential directions to further develop their influencer marketing strategy in the future. Four ideas have been presented in this thesis: (1) Farfetch should invest to develop stronger relationships with the influencers; (2) Farfetch should consider extending its influencer marketing strategy to new platforms such as Tiktok; (3) Farfetch should consider working with sustainable influencers; (4) Farfetch should also analyze the benefits of working with/creating their own virtual influencers. In this study, we realized that influencer marketing is a complex social media strategy that needs to be precisely studied by fashion brands in order to be a great success.